Integrating African Markets into the Global Exchange of Services: A Central African Perspective - (:unkn) unknown (My University, 2013)
Abstract Services liberalisation has gradually become very important for growth in developed and less-developed countries alike and can, as such, be seen as development prospects for sub-Saharan Africa where numerous economic integration attempts are stories of repeated failures. Despite the abundant literature on PTAs, however, little attention has been given to Central Africa Economic and Monetary Community (CEMAC) as a trade bloc. This is an attempt to address that dearth. At a time when “boosting intra-African trade” is gaining currency on the continent, this article tests the compatibility of the potential CEMAC economic integration agreement (EIA) against the background of the existing framework and argues that Central Africa countries would be in a better position to integrate their economies after widening the borders of their individually tiny markets. Analysing the legal discipline behind services Preferential Trade Agreements (PTAs) under the General Agreement on Trade in Services (GATS) and how CEMAC’s agreement fits into this legal landscape, this article further advocates that this sub-group of countries should go beyond the Enabling Clause self-contentment and embark on a deeper (and comprehensive) integration.
Keywords: African Research